Analisis Hubungan Status Gizi dan Anemia pada Pasien Tuberkulosis Fase Intensif dan Lanjutan - Nanik Aryani Putri; Teguh Budiharjo; Moch. Alvin 'Izzuddin; Siti Ulul Azmi (Jaringan Laboratorium Medis, 2026)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis, which enters the human body through the air. Treatment for tuberculosis involves Anti-Tuberculosis Drugs (OAT)—including pyrazinamide, rifampicin, isoniazid, ethambutol, and streptomycin—which may cause side effects that increase the risk of nutritional status changes and anemia. This study analyzes the relationship between nutritional status, anemia status, and the phase of treatment among TB patients in Semarang City.This research employed a descriptive observational design with a cross-sectional approach. Data were obtained from outpatient TB patients at the Bangetayu and Kedungmundu Public Health Centers (Puskesmas). A total of 44 adult subjects without comorbidities were recruited via purposive sampling, comprising 20 patients in the intensive phase and 24 in the continuation phase of treatment. Nutritional status was evaluated using Body Mass Index (BMI), while anemia status was assessed through hematological parameters, including hemoglobin (Hb), hematocrit (Ht), and erythrocyte indices. Statistical analysis revealed no significant correlation between anemia status or hematological parameters (Hb, Ht, erythrocyte indices) and BMI in either treatment group (p>0.05). These findings suggest that hematological profiles may be more heavily influenced by systemic inflammation resulting from tuberculosis (TB) infection or the effects of anti-TB therapy rather than nutritional status alone.Conversely, a significant correlation was identified between BMI and body weight (p<0.001), reflecting the inherent variations in patients' nutritional status. Future studies incorporating a larger sample size and additional variables—such as the duration of TB treatment, disease severity, and dietary intake—are warranted to further elucidate these findings. This study provides an initial contribution to understanding the link between TB, nutritional status, and anemia. Furthermore, platelets and body height showed trends toward significant differences, which may serve as a basis for further research and open opportunities for developing nutrition-based interventions for TB patients.